A novel rosamine-based fluorescent probe for bisulfite in aqueous solution. Issue 106 (1st November 2016) - Zhang, Di; Wenya, Liu; Chen, Keke; Cheng, Junye; Zhao, Yufen; Ye, Yong
Abstract : A new rosamine-based fluorescent chemodosimeter has been developed for highly sensitive and selective detection of bisulfite in aqueous solution. Abstract : A new rosamine-based fluorescent probe (RosCHO ) for bisulfite was obtained by one pot reaction of p -phthalaldehyde and 3-(diethylamino)phenol, which showed excellent selectivity, high sensitivity and a rapid response toward bisulfite in aqueous solution. Upon the addition of HSO3 −, the aldehyde moiety in probe RosCHO formed a hydrogen sulfite-dependent adduct product, leading to fluorescence enhancement due to the different ICT process. The detection limit for bisulfite was as low as 7 × 10 −8 M, and fluorescence imaging of bisulfite in MCF-7 cells demonstrated its value to practical application in biological systems.